PERAN PENYULUH AGAMA ISLAM DALAM PROGRAM PENINGKATAN EKONOMI MASYARAKAT MELALUI PEMBUATAN TELUR ASIN DI DESA MEKAR BARU KECAMATAN PETIR KABUPATEN SERANG - Mohamad Imam Kamaludin (Department of Islamic Community Development, Faculty of Da'wah, State Islamic University (UIN) of Sultan Maulana Hasanuddin Banten, 2021)
Religious instructors have an important role in the community. Islamic religious instructors are usually tasked with providing counseling about religion for the community, but in this case the Islamic Religious Counselors in Serang Regency have their own initiatives by providing counseling on the importance of the economy in religion for the community. Therefore, Islamic religious instructors in Petir District, Serang District, tried to help the government to empower the community, Mekar Baru Village, Petir District with a program to improve the community's economy through making salted eggs. Based on the description above, the formulation of the problem in this study are: 1) Why does the Islamic religious instructor hold a program to improve the community's economy through salted eggs? 2) How is the implementation of the community economic improvement program through the manufacture of salted eggs? 3) What are the supporting and inhibiting factors in the community economic improvement program through the manufacture of salted eggs? This study aims to explain 1) The program to improve the community's economy through salted eggs carried out by Islamic religious instructors in Serang Regency. 2) Knowing the implementation of the community economic improvement program through the manufacture of salted eggs carried out by Islamic religious instructors in Serang Regency. 3) Knowing the supporting and inhibiting factors of the community's economic improvement program through the manufacture of salted eggs. The difference between the research conducted by Nasrullah, Ramadhan, and Wardatul Asriyah with this thesis is about the salted egg, that is, the religious instructor in addition to providing religious counseling guidance also provides an understanding of the importance of maintaining economic stability in religion. This study uses a qualitative descriptive method. For data collection techniques using observation, interviews, and documentation. Based on the research conducted, it can be concluded that the Islamic religious counslors made a salted egg making program to help the economy of the community in Mekar Baru Village. Implementation of the program is divided into 4, namely, daily, weekly, monthly, and yearly. The supporting factors of the program are: the involvement of the management and the community as well as assistance from donors. The inhibiting factors are: lack of transportation between villages, facilities and infrastructure.